2003
DOI: 10.1097/01.hdx.0000061702.79961.47
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender and Reported Alcohol Intake on Mortality in Nonischemic Dilated Cardiomyopathy

Abstract: Between 1994-1998, we retrospectively studied a cohort of 396 consecutive patients with dilated cardiomyopathy, mean age 53 +/- 15 years, 74% men. The history of alcohol intake was abstracted from the medical records. During a follow-up period of 42 +/- 26 months, 83 (76% men) patients died and 15 (80% men) underwent cardiac transplantation. Men were younger and more likely to have a history of excessive alcohol intake compared with women. Gender significantly modified the risk of alcohol consumption on mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…88 Death rates related to alcoholic cardiomyopathy are greater in men than women because of the higher prevalence of alcohol consumption in men, but alcohol intake is associated with a higher mortality risk in women than in men with DCM. 90 The risk of developing alcoholic cardiomyopathy appears to be related to mean daily alcohol intake, duration of drinking, and individual patient characteristics, including genetic susceptibility. In general, alcoholic patients consuming alcohol for >5 years are at risk for the development of alcoholic cardiomyopathy.…”
Section: Epidemiology and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…88 Death rates related to alcoholic cardiomyopathy are greater in men than women because of the higher prevalence of alcohol consumption in men, but alcohol intake is associated with a higher mortality risk in women than in men with DCM. 90 The risk of developing alcoholic cardiomyopathy appears to be related to mean daily alcohol intake, duration of drinking, and individual patient characteristics, including genetic susceptibility. In general, alcoholic patients consuming alcohol for >5 years are at risk for the development of alcoholic cardiomyopathy.…”
Section: Epidemiology and Prognosismentioning
confidence: 99%
“…In patients with alcoholic cardiomyopathy, total abstinence is recommended (Level of Evidence C). [88][89][90][91]94,95 Cocaine-related Cardiomyopathy…”
Section: Key Management Strategies For Alcoholic Cardiomyopathymentioning
confidence: 99%
“…In contrast, in a study of 753 patients admitted to a Veterans Administration facility with HF, the majority of whom had nonischemic LV dysfunction, alcohol consumption was an independent predictor of multiple readmissions for HF (32). Additionally, a study of alcohol consumption in 396 patients with nonischemic LV dysfunction demonstrated a hazard in women, but not in men (33). Some potential limitations of this analysis should be noted.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the impact of alcohol intake on death rate in patients with dilated cardiomyopathy is greater in females than in males. 109 As a tool to identify mechanisms behind this difference, transgenic models exist in which females develop worse cardiac phenotypes than males. For example, both sexes of mice with cardiac-restricted overexpression of platelet-derived growth factor C develop hypertrophy, but only female animals showed dilated cardiomyopathy, heart failure, and sudden death.…”
Section: Cardiac Disease In Which Males Do Not Fare Worse Than Femalesmentioning
confidence: 99%